Developing a Character Education Model Based on Behavior Contracts to Enhance Student Discipline in Elementary School - Yuliyanti Yuliyanti; Abdullah Pandang; Supriadi Torro (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2026)
Elementary school discipline problems often persist despite students' familiarity with school rules, revealing a gap between moral knowing and moral action. This study aimed to develop, validate, and test a character education model based on behavior contracts to improve student discipline at SDN 09 Bungku, Central Sulawesi, Indonesia. Using a research and development design adapted from the Borg and Gall model, data were collected from August to November 2024 through needs analysis (1 principal, 13 teachers, 31 students), expert validation (3 validators), and a practicality-effectiveness trial involving 46 fourth- and fifth-grade students in a one-group pretest-posttest design. The resulting seven-component model—comprising behavioral identification, antecedent-behavior-consequence analysis, target setting, a behavior contract, monitoring, reflection, and follow-up—was rated highly valid by experts (content validity 91.67%; tool validity 89.71%) and highly practical by teachers and students (90.95%). Paired-sample t-test results showed a significant increase in discipline scores from pretest (M = 51.20, moderate) to posttest (M = 78.54, high), t(45) = -26.91, p < .001. Gains were consistent across the moral knowing, moral feeling, and moral action dimensions. These findings suggest that behavior contracts can serve as an operational bridge between character values and observable student conduct in elementary classrooms.